Genomic characterization of the barnacle Balanus improvisus reveals extreme nucleotide diversity in coding regions - Alm Rosenblad, Magnus; Nystedt, Björn (University of Gothenburg, 2021)
Pilot short-read genome assembly of one single adult barnacle, Balanus improvisus (=Amphibalanus imrpovisus), used to estimate genome size and heterocygosity. Bi01.clean.fa.gz is the final assembly with contaminations etc removed.
Alm Rosenblad et al., Marine Biotechnology 2021

Abstract Barnacles are key marine crustaceans in several habitats and they constitute a common practical problem by causing biofouling on man-made marine constructions and ships. Despite causing considerable ecological and economic impacts, there is a surprising void of basic genomic knowledge, and a barnacle reference genome is lacking. We here set out to characterize the genome of the bay barnacle Balanus improvisus (= Amphibalanus improvisus) based on short-read whole genome sequencing and experimental genome size estimation.
We show both experimentally (DNA staining and flow cytometry) and computationally (k-mer analysis) that B. improvisus has a haploid genome size of ~ 740 Mbp. A pilot genome assembly rendered a total assembly size of ~600 Mbp and was highly fragmented with an N50 of only 2.2 kbp. Further assembly-based and assembly-free analyses revealed that the very limited assembly contiguity is due to the B. improvisus genome having an extremely high nucleotide diversity (π) in coding regions (average π ≈ 5% and average π in 4-fold degenerate sites ≈ 20%), and an overall high repeat content (at least 40%). We also report on high variation in the α-octopamine receptor OctA (average π = 3.6%), %), which might increase the risk that barnacle populations evolve resistance towards antifouling agents. The genomic features described here can help in planning for a future high-quality reference genome, which is urgently needed to properly explore and understand proteins of interest in barnacle biology and marine biotechnology and for developing better antifouling strategies.
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik